DEVELOPMENT OF EVALUATION TOOLS USING QUIZIZZ APPLICATION IN MATHEMATICS - Chrisnaji Banindra Yudha; Risky Dwiprabowo; Budiono (Pusat Riset dan Inovasi Nasional, 2022)
Internet technology is indispensable today for the distance learning process. In order for the material to be delivered even though it is distance learning, the teacher must be creative in this regard. Fourth grade teachers at SDN Jatirangga 3 Bekasi use an easy-to-use application to track students during the learning process. Besides being able to help teachers, students are also more enthusiastic when learning through the applications used. The purpose of this study is to develop an evaluation tool using the Quizizz application. research methods used to produce a particular product, and test the effectiveness of that product. The development of an evaluation tool in the form of an online test using the Quizizz application in the Mathematics subject arithmetic operations with integers gets a percentage of 80% in the appropriate category and media experts get a percentage of 85% in the very feasible category. Evaluation validation obtained 6 invalid questions and 14 valid questions, reliability obtained 0.801, Student assessment responses to the evaluation tool using the quizizz application get a very interesting percentage of information of 84.67%. The final product in this research and development is 14 questions to develop an evaluation tool in the form of an online test using the Quizizz application in Mathematics, integer arithmetic operations for grade IV elementary school.